Microbiome-host interactions in the pathogenesis of acute exacerbation of chronic obstructive pulmonary disease - Li, Yao; Mao, Xiaoyan; Shi, Pengfei; Wan, Zongren; Yang, Dan; Ma, Ting; Wang, Baolan; Wang, Jipeng; Wang, Jingjing; Zhu, Rong (Frontiers in Cellular and Infection Microbiology, 2024)
Objective To explore the underlying mechanisms the airway microbiome contributes to Acute Exacerbation of Chronic Obstructive Pulmonary Disease(AECOPD). Methods We enrolled 31 AECOPD patients and 26 stable COPD patients, their sputum samples were collected for metagenomic and RNA sequencing, and then subjected to bioinformatic analyses. The expression of host genes was validated by Quantitative Real-time PCR(qPCR) using the same batch of specimens. Results Our results indicated a higher expression of Rothia mucilaginosa(p=0.015) in the AECOPD group and Haemophilus influenzae(p=0.005) in the COPD group. The Different expressed genes(DEGs) detected were significantly enriched in "type I interferon signaling pathway"(p<0.001, q=0.001) in gene function annotation, and "Cytosolic DNA-sensing pathway"(p=0.002, q=0.024), "Toll-like receptor signaling pathway"(p=0.006, q=0.045), and "TNF signaling pathway"(p=0.006, q=0.045) in KEGG enrichment analysis. qPCR amplification experiment verified that the expression of OASL and IL6 increased significantly in the AECOPD group. Conclusion Pulmonary bacteria dysbiosis may regulate the pathogenesis of AECOPD through innate immune system pathways like type I interferon signaling pathway and Toll-like receptor signaling pathway.